Hepatitis E Vaccine Trial in the Royal Nepal Army - Shrestha, Mrigendra P; Scott, Robert McNair; Malla, Laxmi Ram; Joshi, Durga Man; Shrestha, Khagendra Bahadur; Rayamajhi, Krishna Narsingh (Medical Journal of Shree Birendra Hospital, 2001)
Hepatitis E Vaccine Trial in the Royal Nepal Army